Innovative approaches to managing longevity risk in Asia: Lessons from the West - Amlan Roy (Asian Development Bank Institute (ADBI), 2012)
This paper discusses what is longevity risk, why it is important, approaches used by the West to manage longevity risk and what lessons can be learnt by Asian countries from the experiences of the West. Increasing and uncertain longevity has emerged as a key risk affecting individuals, pension plans, insurers and governments in both the developed and emerging world. I discuss progress in the field of longevity modelling and the merits as well as drawbacks of these models. In Western countries, attempts have been made by capital market and governments to deal with longevity risk, but the availability of solutions remain limited. Further developments should focus on creating a set of instruments that are effective, economically affordable, and transparently priced. It is important to understand, measure, and manage longevity risk. Moreover, further pension reforms are needed to address the root of the problem. For Asian countries, the experience of the West provides ample guidance in formulating their pension plans and promoting capital market developments to avoid the same predicament the West is now struggling with. Simple cost-effective solutions linking retirement ages to longevity, efficiently engaging women and older workers in the work force for longer, education and technology driven flexible work practices, along with preventing productive human capital outflows ought to be considered seriously in Asia.
Keywords: G17; G22; G23; E24; 330; longevity risk; asia; managing longevity risk; longevity modeling; pension plans; Sterblichkeit; Risiko; Alternde Bevölkerung; Gesundheit; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Industrieländer; Vergleich; Asien